Depressive Symptoms among Latino Sexual Minority Men and Latina Transgender Women in a New Settlement State: The Role of Perceived Discrimination. (14th September 2016) - Sun, Christina J.; Ma, Alice; Tanner, Amanda E.; Mann, Lilli; Reboussin, Beth A.; Garcia, Manuel; Alonzo, Jorge; Rhodes, Scott D.
Abstract : Background. Little is known about the role of discrimination on depression among Latino sexual and gender identity minorities. This manuscript examined the relationship between ethnic/racial discrimination and sexual discrimination on clinically significant depressive symptoms among Latino sexual minority men (i.e., gay and bisexual men and other men who have sex with men) and Latina transgender women. Methods. A community-based participatory research partnership recruited participants (N = 186; 80.6% cisgender men) in North Carolina to a social network-based HIV intervention. Using baseline data, we quantified the amount of perceived discrimination and conducted mixed-effects logistic regression analyses to examine correlates of clinically significant depressive symptoms. Results. A high percentage of participants reported ethnic/racial discrimination (73.7%) and sexual discrimination (53.8%). In the multivariable models, ethnic/racial discrimination, sexual discrimination, masculinity, fatalism, and social support were significantly associated with clinically significant depressive symptoms. Discussion. Improving mental health requires multilevel interventions that address pertinent individual, interpersonal, and system level factors.